REPRESENTATION OF THE INDIVIDUAL AUTHOR’S WORLD-VIEW IN THE WORK OF HENRY JAMES (BASED ON KEY AUTHOR’S CONCEPTS) - YUliya A. Demkina (Moscow Region State University Editorial Office, 2021)
<!DOCTYPE html> Aim. Identification of linguistic and stylistic representational means of the individual author’s picture of the world in the works of Henry James. Methodology. The main content of the research is the analysis of the key-author’s concepts in the work of Henry James and the means of their representation. The methods of conceptual analysis, component-semantic analysis, generalization of dictionary definitions, continuous sampling method, logical method, and comparative method were used in the study. Results. Stylistic techniques of objectification of the concepts “depravity”, “hypocrisy”, “experience” are identified. expressiveness, used to create implicit information in a poetic text, is analysed. Research implications. The results of the study contribute to linguoconceptology.